2021
DOI: 10.1155/2021/6683411
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Mechanism of Natural Product Ingredients in the Treatment of Uveitis

Abstract: As the spectrum of ophthalmic diseases keeps changing, uveitis has gradually become one of the major blinding eye diseases in the world. Although the efficacy and safety of adalimumab and other biological agents in the treatment of uveitis have been proved in clinical studies, no biological agents have been approved for the treatment of uveitis by Chinese National Medical Products Administration (NMPA). The quality of life and prognosis of uveitis patients are affected by the adverse reactions of currently ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Anti-TNF agents and monoclonal antibodies, including Adalimumab, Infliximab, and Daclizumab, are often necessary for the treatment of chronic, non-infectious patients, especially in ones associated with systemic inflammatory diseases [ 95 ]. Herbal remedies may also be considered for treating uveitis [ 96 ].…”
Section: Therapeutic Uses In Eye Diseasesmentioning
confidence: 99%
“…Anti-TNF agents and monoclonal antibodies, including Adalimumab, Infliximab, and Daclizumab, are often necessary for the treatment of chronic, non-infectious patients, especially in ones associated with systemic inflammatory diseases [ 95 ]. Herbal remedies may also be considered for treating uveitis [ 96 ].…”
Section: Therapeutic Uses In Eye Diseasesmentioning
confidence: 99%
“…T. wilfordii glycosides, such as triptolide, celastrol, and wilforlide A, can exert anti-inflammatory effects by inhibiting the p56 subunit of the NF-κB signaling pathway, as well as by downregulating the expression of inflammatory factors such as TNF and IFN (Li et al, 2021). Studies have shown that NOD-like receptor protein 3 (NLRP3)-induced inflammation plays a key role in RA pathogenesis, and treatment with T. wilfordii has been demonstrated to inhibit activation of the NLRP3 inflammasome by blocking the NF-κB signaling pathway, thereby contributing reductions in joint swelling, arthritis index score, inflammatory cell infiltration, and synovial hyperplasia induced by complete Freund's adjuvant in rats (Jing et al, 2023).…”
Section: Tripterygium Wilfordii and Its Derivatives Inhibit Ra-associ...mentioning
confidence: 99%